2011
DOI: 10.1371/journal.pone.0025644
|View full text |Cite
|
Sign up to set email alerts
|

FACT, the Bur Kinase Pathway, and the Histone Co-Repressor HirC Have Overlapping Nucleosome-Related Roles in Yeast Transcription Elongation

Abstract: Gene transcription is constrained by the nucleosomal nature of chromosomal DNA. This nucleosomal barrier is modulated by FACT, a conserved histone-binding heterodimer. FACT mediates transcription-linked nucleosome disassembly and also nucleosome reassembly in the wake of the RNA polymerase II transcription complex, and in this way maintains the repression of ‘cryptic’ promoters found within some genes. Here we focus on a novel mutant version of the yeast FACT subunit Spt16 that supplies essential Spt16 activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 104 publications
0
11
1
Order By: Relevance
“…This was suggested to stem from a direct effect of H2Bub1 on FACT, but our data suggest that it could reflect impaired function of Clr6-CII. Evidence of opposing functions of FACT and Rpd3S in S. cerevisiae is consistent with this possibility ( 63 ).…”
Section: Discussionmentioning
confidence: 65%
“…This was suggested to stem from a direct effect of H2Bub1 on FACT, but our data suggest that it could reflect impaired function of Clr6-CII. Evidence of opposing functions of FACT and Rpd3S in S. cerevisiae is consistent with this possibility ( 63 ).…”
Section: Discussionmentioning
confidence: 65%
“…3). Indeed, aberrant intragenic transcription was first identified in mutants of the Spt6 and Spt16 (FACT) histone chaperones, known to play a role in nucleosome reassembly during transcription elongation [136, 155, 156]. Similar findings were also obtained for a Rtt106-deficient strain: Rtt106 is a histone chaperone associated with coding sequences and involved in histone H3 deposition over ORFs [154, 157].…”
Section: Maintenance Of Genome Integritymentioning
confidence: 77%
“…Mutations in SPT16 made the promoter of SER3 accessible for transcriptional factors and therefore derepressed the SER3 gene [78]. Multiple subsequent studies have reported loss of nucleosomes from transcribed genes in a transcription-dependent manner following yFACT depletion, which was accompanied by the appearance of short transcripts that originated from cryptic TSSs within the coding regions of yeast genes [66,[78][79][80][81][82][83][84][85]. FACT was also shown to be a critical factor in the repression of cryptic initiation of intragenic promoters genome-wide in plants [86].These data cumulatively suggest that in vivo, yFACT is clearly important for preserving chromatin structure at transcribed genes.…”
Section: Fact In Transcriptionmentioning
confidence: 99%